Enhancing Grammar Instruction in Maritime Academy: A Case Study on Quizzes-Based Reading Comprehension Tasks - hadi wibowo, amiruddin; Yovita Suryarini, Diah (Universitas Nahdatul Ulama Surabaya, 2024)
Gamification significantly enhances students' engagement and motivation, leading to better language learning outcomes. Quiziz-basedtasks are accessible and convenient, increasing students' engagement and motivation in language learning. A case study research design was used in this article to describe the implementation of Quiziz-based tasks in teaching grammar in Maritime Academy. The participants of the study were 30 EFL students from a private university. The study aimed to examine the effectiveness of Quiziz-basedtasks in improving the grammar knowledge and proficiency of the EFL students. The result shows that Students find Quiziz-basedtasks helpful for learning grammar, as they are interactive, engaging, and customized to target specific grammar points. The interactive and personalized nature of Quiziz-basedtasks, along with immediate feedback, contribute to students' improvement in grammar knowledge and proficiency. Thus, use of Quiziz-basedtasks in Maritime Academy enhances grammar instruction by increasing student engagement, motivation, and knowledge of grammar rules. and encourages students to actively participate in the learning process.